ÁLVAREZ, Eduardo (2021). Las ideas filosóficas de Marx. Madrid: Tecnos. - Ribas Ribas, Pedro (Daimon Revista Internacional de Filosofia, 2022)
Reseña de: ÁLVAREZ, Eduardo (2021). Las ideas filosóficas de Marx. Madrid: Tecnos.